The performance of correlative coding in MIMO-OFDM systems - Syed-Yusof, Sharifah K.; Fisal, Norsheila; Muladi, Muladi (2005)
This paper considers the use of frequency-domain correlative coding in MIMO-OFDM systems to improve the BER caused by channel frequency offset. At BER of 104, the E,/N0 needed managed to be reduced by 2-4 dB when correlative coding was used in MIMO-OFDM systems with the presence of frequency offset, e=0.15.